Effect of Digoxin on the Color Vision Disorder, A Case-Control Study - Toba Kazemi; Mohammad Hossien Davari; Hanie Afrazande (Journal of Basic & Applied Sciences, 2021)
Background and Aim: Digoxin is a drug commonly used in order to treat cardiac failure but its use has got different complications including color vision disorder .Regarding the high prevalence of cardiac failure and the role of taking this drug by patients, it was decided to study color vision disorder in patients who take digoxin. Materials and Methods: The present case-control study was conducted during 2008-2009 in Valli-e-asr hospital in Birjand.The case group consisted of 59 patients having cardiac failure who, at least, had taken oral digoxin for one year. The controls were non-cardiac patients referring to the hospital or were patients’ attendants who did not take digoxin. The controls were matched with the cases with respect to age and sex. Both groups were examined regarding whether they had color vision disorder or not by means of Ishiharatest. Venous blood was derived from all the cases to assess serum digoxin level. Then, the obtained data was an encoded and statistically analysed by means of SPSS software at the significant level α=0.05. Findings:In this survey, 59 patients with Heart failure who took digoxin and 59 controls were studied. Relative frequency of color vision disorder in the cases was estimated at 6.8%, but in the controls it was estimated at 1.7%; hence the difference was not statistically significant (P=0.36).Frequency of color vision disorder did not reveal a significant difference regarding age and sex. Serum digoxin level was abnormal in 5.1% of the patients. A significant difference was not found between mean serum digoxin and color vision disorder. Results:Using color vision disorder, as a diagnostic measure of Digoxin toxicity, is of no use.